2007
DOI: 10.1088/0953-8984/19/37/376108
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a shape-dependent density maximum in random packings and glasses of colloidal silica ellipsoids

Abstract: We have measured the random packing density of monodisperse colloidal silica ellipsoids with a well-defined shape, gradually deviating from a sphere shape up to prolates with aspect ratios of about 5, to find for a colloidal system the first experimental observation for the density maximum (at an aspect ratio near 1.6) previously found only in computer simulations of granular packings. Confocal microscopy of ellipsoid packings, prepared by rapidly quenching ellipsoid fluids via ultra-centrifugation, demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
93
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(99 citation statements)
references
References 25 publications
6
93
0
Order By: Relevance
“…For example, the presented method can be applied to a suspension of bidisperse colloids [39,40]. Another possible extension lies in the use of nonspherical hard colloids, for example, fluorescent rods [41,42], or polyhedral colloids [43] where exactly the same concepts can be applied. Constructing the available volume and its surface area then becomes more cumbersome, but in principle possible.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the presented method can be applied to a suspension of bidisperse colloids [39,40]. Another possible extension lies in the use of nonspherical hard colloids, for example, fluorescent rods [41,42], or polyhedral colloids [43] where exactly the same concepts can be applied. Constructing the available volume and its surface area then becomes more cumbersome, but in principle possible.…”
Section: Discussionmentioning
confidence: 99%
“…These shape characteristics strongly affect the rheology and texture of granular materials. This has been recently evidenced by a number of numerical and experimental studies carried out using angular particles [1][2][3][4][5][6][7][8][9][10][11][12] and by a number of investigations that have focused on other important characteristics such as elongation [13][14][15][16][17][18][19][20] or non-convexity [21,22]. The existing research results suggest that the effect of shape parameters is often nonlinear and counterintuitive as in the case of the unmonotonic relation between the elongation of the particles and the packing fraction [13,14,18].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, even if an increasing number of experimental and numerical studies have shown that the grain shape considerably affects the quasistatic behavior of granular materials [4,[6][7][8][9], systematic and quantitative investigations of shape or mixture of shape effects are still elusive. One of the difficulties is that the shape parameters mentioned above need to be defined conveniently in order to be able to generate particle shapes with continuouslyvariable shape parameters.…”
Section: Introductionmentioning
confidence: 99%